Shear Strain Model for Equal Channel Angular Pressing in High Elastic Extruded Plastics - Anjum, N. A.; Khan, M. Z.; Shah, M.; Khalil, M. S.; Pasha, R. A.; Qayyum, F.; Anwar, W. (The Nucleus, 2015)
This paper presents a novel model for plastic shear strain calculation in the Equal Channel Angular Pressing (ECAP). The model is particularly formulated to furnish for the elastic recovery after extrusion. Due to high elastic recovery after plastic deformation in polymers, the behavior of Teflon and Nylon is investigated at different temperatures as they are famous for their low coefficient of friction and wall friction effects. The main concentration is given to the basic principle of ECAP processing parameters such as strain, slip bands, and shearing patterns. In this research, a new engraved circle marking technique is used to trace the plastic deformation in the specimens. Afterwards, image analysis approach is applied to measure the deformation, strain and rotation after extrusion. The experimental results are validated with the ABAQUS based numerical simulation. A close conformity is found between them.